2019
DOI: 10.4103/aam.aam_17_18
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body mass index and gender on lipid profile in children and adolescents in Saudi Arabia

Abstract: Objectives:The objectives of this study were to study the relationship between lipid profile components among different body mass index (BMI) groups and investigate the association between gender and BMI.Methodology:This cross-sectional study included 218 children and adolescents; 104 males and 114 females. Accepted age range was from 2 to 18 years. Data were collected from February to May during the year of 2017 and were analyzed using the Statistical Package for the Social Sciences. Standard deviation (SD) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
4
4
0
Order By: Relevance
“…Gender was also significantly with dyslipidemia in other studies [11][12][13][14] , but a recent study did not show a significant relationship between gender and dyslipidemia 15 , which supports our findings. We think that due to lack of large number of participants in this study, the relationship between gender and dyslipidemia may be not able to be generalized.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Gender was also significantly with dyslipidemia in other studies [11][12][13][14] , but a recent study did not show a significant relationship between gender and dyslipidemia 15 , which supports our findings. We think that due to lack of large number of participants in this study, the relationship between gender and dyslipidemia may be not able to be generalized.…”
Section: Discussionsupporting
confidence: 90%
“…Gender was significantly correlated with dyslipidemia 11 . In a recent study by Milyani and Al-Agha 15 , no significant relationship was proved between dyslipidemia and gender.…”
Section: Introductionmentioning
confidence: 87%
“…The mean TC and LDL-C levels in our study correspond to the mean TC and LDL-C levels in morbidly obese children in that study [18]. Additionally, the study found no significant differences in metabolic profiles between genders and age groups, which is similar to another study [18].…”
Section: Discussionsupporting
confidence: 89%
“…In Saudi Arabia, a local study demonstrated that a high body mass index (BMI) was linked to increased LDL levels and decreased HDL levels in children aged two to 18 years old [ 18 ]. Among children in Riyadh recently diagnosed with diabetes, a study showed that 64% were overweight or obese, and 34% exhibited signs of insulin resistance [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Al-Agha et al (2019), [13] conducted a study to assess the relationship between lipid profile components among different body mass index (BMI) groups. They included 218 children and adolescents of which 104 were males and 114 were females.…”
Section: Discussionmentioning
confidence: 99%